(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The industrial revolution which took place in the 18th and 19th centuries changed the scenario of the world with greater and efficient industrial production with the help of machines. The revolution was powered by fossil fuels, which has turned out to be the biggest menace for the planet in modern times. Water pollution is regarded as a major type of pollution. We are living in an environment contaminated with different pollutants. Pollutants are entering different biogeochemical cycles and ecosystems and making them unsuitable for life. Surface water is more vulnerable to pollution than underground water. Agriculture and industrial waste such as pesticides, fertilizers, toxic chemicals, and heavy metals are often discharged into rivers untreated, thereby contaminating these freshwater sources. A pollutant is defined as a substance that is present in the environment that may harm flora and fauna or environmental quality standards (Kumar, 1995). Water pollution is a hot topic of international and national debate and a vast domain related to many types of pollutants entering the hydrological cycle account as water pollutants. River water, lakes, ponds, underground water, as well as seawater contamination are all subjects under the broader subject of water pollution. The current research deals with the contamination of freshwater by heavy metals.